2021
DOI: 10.1177/00333549211015662
|View full text |Cite
|
Sign up to set email alerts
|

Using Surveillance With Near–Real-Time Alerts During a Cluster of Overdoses From Fentanyl-Contaminated Crack Cocaine, Connecticut, June 2019

Abstract: In 2019, Connecticut launched an opioid overdose–monitoring program to provide rapid intervention and limit opioid overdose–related harms. The Connecticut Statewide Opioid Response Directive (SWORD)—a collaboration among the Connecticut State Department of Public Health, Connecticut Poison Control Center (CPCC), emergency medical services (EMS), New England High Intensity Drug Trafficking Area (HIDTA), and local harm reduction groups—required EMS providers to call in all suspected opioid overdoses to the CPCC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
0
9
0
3
Order By: Relevance
“…One study reported ODMAP's successful use in an outbreak of cocaine‐related deaths associated with fentanyl in Connecticut (one of the sites we were unable to interview). ODMAP's geocoding and pinpoint mapping functionality helped target a specific neighborhood leading to a full epidemiologic investigation once an outbreak was suspected (Canning et al., 2021). That study was consistent with our findings that ODMAP is considered a valuable tool for geocoding and mapping.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported ODMAP's successful use in an outbreak of cocaine‐related deaths associated with fentanyl in Connecticut (one of the sites we were unable to interview). ODMAP's geocoding and pinpoint mapping functionality helped target a specific neighborhood leading to a full epidemiologic investigation once an outbreak was suspected (Canning et al., 2021). That study was consistent with our findings that ODMAP is considered a valuable tool for geocoding and mapping.…”
Section: Discussionmentioning
confidence: 99%
“…From a research standpoint, it is imperative to continue examining the confounding influence of the COVID-19 pandemic on individuals who are at risks resulting from NPF as the combined crisis could lead to increased health disparities over time [ 46 ] especially for ethnic minority populations [ 47 ] and those experiencing homelessness [ 48 ]. Lastly, research efforts that seek to develop and test new means of community-wide surveillance will become critical [ 49 ] for the development of a more timely and geographically targeted delivery of harm reduction services and interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to potential data breaches, the sharing of information about PWUD between public health, law enforcement, and the criminal legal system represents another troubling example of surveillance health data being used in problematic ways. Take, for example, the Connecticut Statewide Opioid Response Directive (or “SWORD”) where near-real-time localized overdose surveillance data gathered by Emergency Medical Services and shared with public health was subsequently made accessible to local police who used the information to target and arrest people who use and sell drugs ( Canning et al, 2021 ; see also Michaud et al, 2022 ). This example illustrates how information collected for “health” reasons becomes repurposed in service of prohibition and interdiction efforts.…”
Section: Potential Implications For Pwudmentioning
confidence: 99%
“…Data collection can be primarily benign, motivated by establishing reach of services, managing inventory of resources, or other operational concerns. In other instances, however, public health officials have provided bio-behavioral overdose “hot spot” surveillance data to police services which use the information to target and arrest PWUD ( Canning et al, 2021 ). In this way, surveillance in harm reduction can actuate both “care” and “control” ( Moore, 2011 ).…”
mentioning
confidence: 99%